“M-Six Craft” Fashion Ecoprint Product Packaging Design Training - UMKM Marinda, Manyar Indah, Surabaya - Widyasari; Sri Wulandari; Aditya Rahman Yani; Handy Octoriawan; Mochammad Al-Hadad Firmansyah (Nusantara Science and Technology Proceedings, 2021)
The Surabaya City Government annually has programs in developing the City of Surabaya, one of which is the "Smart City" program which is a program with the aim of developing the City of Surabaya as an advanced city in the fields of economy and technology. The Surabaya City “Smart City” program increases the motivation of the people of Surabaya City to make their area more productive and competitive. One of the efforts to increase residents' productivity and increase regional competitiveness is carried out by residents of Manyar Indah, RW 06, Menur Pumpungan urban village, Sukolilo sub-district, Surabaya City by developing ecoprint -based fashion products. Furthermore, the ecoprint fashion product chose the name "M-Six Craft" as their brand identity. “M-Six Craft” is part of the Manyar Indah Small, Micro and Medium Enterprises (UMKM Marinda). Researchers saw that the terms quality of the product “M-Six Craft” is good but less so in terms of packaging potentially decrease the marketability and competitiveness of products in the industry, especially in the field of fashion. This research is based on community service activities by providing training on making packaging design for “M-Six Craft” ecoprint fashion products – UMKM Marinda, Manyar Indah, Surabaya, with considerations including: easy to teach and train, “M-Six Craft“ UMKM ecoprint fashion products have not been packaged. well and interestingly. Activities community service -based study of the mob. The methods used during the activities include presentation, demonstration and practice methods. The results achieved in this outreach activity were providing information and knowledge about product packaging, discussions with UMKM Marinda and making packaging designs for “M-Six Craft” ecoprint fashion products.